1995
DOI: 10.1016/0042-6989(95)00082-p
|View full text |Cite
|
Sign up to set email alerts
|

Voluntary binocular gaze-shifts in the plane of regard: Dynamics of version and vergence

Abstract: We studied the dynamics of voluntary, horizontal, binocular gaze-shifts between pairs of continuously visible, real three-dimensional targets. Subjects were stabilized on a biteboard to allow full control of target angles, which were made to differ only in distance (pure vergence), only in direction (pure version; conjugate saccades) or in both distance and direction (disjunctive saccades). A wide range of changes in vergence (0-25 deg) and version (0-65 deg) was recorded to study the dynamics of disjunctive s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
132
2
6

Year Published

1999
1999
2011
2011

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(147 citation statements)
references
References 32 publications
(55 reference statements)
7
132
2
6
Order By: Relevance
“…However, numerous studies have provided results that argue against this view. Vergence velocities are greater than what would be predicted by a linear summation of a conjugate saccade with a saccade-free vergence movement, while conjugate velocities are decreased Mays 2003, 2005a;Collewijn et al 1995Collewijn et al , 1997Enright 1984Enright , 1992Erkelens et al 1989; Kenyon et al 1980;Kumar et al 2005;Maxwell and King 1992;Ono et al 1978;Oohira 1993;Zee et al 1992). Moreover, the amount of vergence facilitation is dependent on peak saccadic velocity (Busettini and Mays 2005a).…”
Section: Introductionmentioning
confidence: 82%
“…However, numerous studies have provided results that argue against this view. Vergence velocities are greater than what would be predicted by a linear summation of a conjugate saccade with a saccade-free vergence movement, while conjugate velocities are decreased Mays 2003, 2005a;Collewijn et al 1995Collewijn et al , 1997Enright 1984Enright , 1992Erkelens et al 1989; Kenyon et al 1980;Kumar et al 2005;Maxwell and King 1992;Ono et al 1978;Oohira 1993;Zee et al 1992). Moreover, the amount of vergence facilitation is dependent on peak saccadic velocity (Busettini and Mays 2005a).…”
Section: Introductionmentioning
confidence: 82%
“…Furthermore, latencies were slightly longer when the eye moved to the right (258 vs. 245 ms; P`0X005). This is caused by measuring the orientation of the left eye only and the fact that temporally directed saccades are somewhat faster than nasally directed saccades (Collewijn, Erkelens, & Steinman, 1995). The ANOVA showed that besides these main eects only interaction eects with sign (left±right) were signi®cant.…”
Section: Latenciesmentioning
confidence: 99%
“…In studies with humans, horizontal saccades during vergence often showed slower velocities and resulted in longer durations than conjugate saccades of comparable size (Collewijn et al 1995;Erkelens et al 1989) but the effects of vergence on vertical saccades were less clear (van Leeuwen et al 1998). In monkeys, superior colliculus (tectal) long lead bursters (TLLBs) show reduced activity for both horizontal and vertical saccades during vergence (Walton and Mays 2003) and we have preliminary evidence (unpublished observations) that this is also seen in medium lead burst neurons (MLBs).…”
Section: Opns and Saccadic Slowingmentioning
confidence: 99%
“…Several studies (Collewijn et al 1995;Erkelens et al 1989;van Leeuwen et al 1998) have noted that horizontal saccades are often slowed when combined with vergence eye movements. Such mixed saccadic-vergence movements are typical of refixations in depth.…”
Section: Introductionmentioning
confidence: 99%